2004
DOI: 10.4049/jimmunol.173.2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Regulates the Kinetics and Receptor Specificity of Staphylococcus aureus Binding to Activated Platelets

Abstract: The interaction between surface components on the invading pathogen and host cells such as platelets plays a key role in the regulation of endovascular infections. However, the mechanisms mediating Staphylococcus aureus binding to platelets under shear remain largely unknown. This study was designed to investigate the kinetics and molecular requirements of platelet-S. aureus interactions in bulk suspensions subjected to a uniform shear field. Hydrodynamic shear-induced collisions augment platelet-S. aureus bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Aggregation phenomena occur in a wide range of fields and the basic mathematical model for such phenomena, the Smoluchowski coagulation equations 1 , has been employed in such disparate fields as aerosols [7], meteorology [17], chemically dispersive systems [24], algal dynamics [2,18], immunology [13], and planetesimal evolution [11]. The seminal ideas were originally developed in the early 1900's by von Smoluchowski to model the rapid aggregation of colloids.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation phenomena occur in a wide range of fields and the basic mathematical model for such phenomena, the Smoluchowski coagulation equations 1 , has been employed in such disparate fields as aerosols [7], meteorology [17], chemically dispersive systems [24], algal dynamics [2,18], immunology [13], and planetesimal evolution [11]. The seminal ideas were originally developed in the early 1900's by von Smoluchowski to model the rapid aggregation of colloids.…”
Section: Model Developmentmentioning
confidence: 99%
“…The fit, however, left much to be desired, and thus in the absence of higher resolution measurements, we assumed a bi-exponential for the shape of the initial density (13) Since we know the initial biomass B 1 , we can identify C 1 (14) To identify the other three parameters, we minimized over γ 1 , C 2 , and γ 2 , where b 0 is defined in (13) and C 1 is defined in (14). We employed the sequential quadratic programming method with inequality constraints and BFGS Hessian update in Matlab's fmincon, supplying it with the analytically computed gradient.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…All of the early S. aureus studies were carried out under static or non-physiological stirring conditions and therefore it is difficult to relate these studies to the disease processes. Studies using a cone and plate viscometer (a device that shears cells at a given flow rate) have demonstrated that protein A, ClfA, SdrC, SdrD and SdrE are important in thrombus formation (George et al, 2007;George et al, 2006;Pawar et al, 2004). However, extremely high shear rates were used in these rheological studies.…”
Section: Platelet-bacterial Interactions: the Staphylococcusmentioning
confidence: 99%
“…Platelets express a high affinity vonWillebrand factor receptor called GPIbα (Andrews et al, 2003). Under very high shear conditions, Pawar and colleagues demonstrated that deletion of SpA from S. aureus significantly reduced its interaction with platelets (Pawar et al, 2004). Furthermore, preincubating platelet rich plasma with a vonWillebrand Factor antibody or indeed blocking the platelet GPIbα receptor with an inhibitory monoclonal antibody partially inhibited the platelet-S. aureus interaction (Pawar et al, 2004 Serine rich protein SraP is a 227kDa large protein and a member of the highly conserved family of serine rich surface glycoproteins expressed on the cell wall of S. aureus .…”
Section: Platelet-bacterial Interactions: the Staphylococcusmentioning
confidence: 99%
See 1 more Smart Citation